Where Economics Went Wrong: A Review Essay - Johnson, Marianne (Journal of Economic Literature, 2020)
In their recent book, Where Economics Went Wrong, David Colander and Craig Freedman (2019) argue that economics went wrong when it abandoned the Classical liberal firewall that demanded separation of scientific theory from the art of policy making. Colander has long advanced the idea that applied economics should be classified neither as positive nor as normative economics. Instead, it should be placed in a third category, “the art of economics”; art requires vision and acumen in addition to knowledge and technique, and is thus more akin to engineering than the natural sciences. The primary contribution of Where Economics Went Wrong is thus to advance Colander’s general argument through the specific story of Chicago economics. This essay make two interconnected claims. First, while I agree with Colander and Freedman that applied economics would benefit from more art and less calculation, the Chicago school is not the best vehicle by which to tell a convincing story. Second, a thicker history of the Chicago school reminds us of the importance of institutions and rules, not only for understanding the economy but also for thinking about how economists have constructed our discipline and how internal institutions and incentives affect our behavioral choices. ( JEL A11, B20, B41, B52)